Amorphous nano oxide and preparation method thereof, negative electrode, battery and electric equipment
The preparation of amorphous nanooxides by ozone etching of metal organic framework materials has been solved, and the problems of poor structural instability and cycle stability of transition metal oxide negative electrode materials have been achieved, and the high capacity retention rate and cycle performance of lithium-ion batteries have been achieved.
Patent Information
- Application Number
- CN202411610331.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
When existing transition metal oxides are used as negative electrode materials for lithium-ion batteries, there are problems of structural instability and poor cycle stability, resulting in battery capacity degradation and performance degradation.
The method of ozone etching metal organic framework materials is used to prepare amorphous nanooxides as the negative electrode material of lithium-ion batteries, and the diffusion ability of lithium ions is improved using its nanosize and porous structure.
By improving the structural stability and cyclic stability of the negative electrode material, the capacity retention rate and cyclic performance of the lithium-ion battery are improved, and the service life of the battery is extended.
Smart Images

Figure CN119490232A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to an amorphous nano-oxide and a preparation method thereof, a negative electrode, a battery and electrical equipment. Background Art
[0002] Energy storage technology is the cornerstone of modern society, especially in the fields of mobile electronic devices and electric vehicles, where efficient and reliable energy supply is essential for the continued advancement of these technologies. Lithium-ion batteries have become an important energy supply option in these fields due to their high energy density, long life and good environmental stability. With the development of science and technology, the requirements for battery performance are also increasing, which has prompted researchers to continuously explore and develop new electrode materials to improve battery performance.
[0003] Among many electrode materials, transition metal oxides have attracted wide attention due to their high theoretical specific capacity and good safety. These materials include Fe2O3, Fe3O4, CuO, NiO, CoO, etc., which can be used as negative electrode materials for lithium-ion batteries. During the charging process, lithium ions are deintercalated from the positive electrode and transferred to the negative electrode through the electrolyte, reacting with the transition metal oxide to form lithium alloy or inserting into its lattice to achieve energy storage. In particular, Fe2O3, as a negative electrode material for lithium-ion batteries, has a theoretical specific capacity of up to 1005mAh / g, which is much higher than the theoretical lithium storage capacity of traditional graphite negative electrode materials.
[0004] However, there are some significant problems and challenges in the prior art when using these transition metal oxides as negative electrode materials for lithium-ion batteries. A major problem is that these materials undergo large volume changes during the process of lithium insertion and extraction. This volume change may lead to instability in the material structure, which in turn causes structural collapse. The collapse of the structure will cause some active materials to lose effective electrical contact with the electrode during the battery charge and discharge cycle, resulting in a gradual decay of the battery capacity.
[0005] In addition, due to the instability of the structure, the cycle stability of the battery is also affected. After multiple charge and discharge cycles, the performance of the battery will drop significantly, which limits its service life and reliability in practical applications. These problems not only affect the energy density and power density of the battery, but also pose challenges to the safety and environmental adaptability of the battery. Therefore, how to improve the structural stability and cycle stability of transition metal oxides as negative electrode materials for lithium-ion batteries is a key issue that needs to be solved in current research.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide an amorphous nano-oxide and a preparation method thereof, a negative electrode and electrical equipment. The oxide material prepared by the preparation method is an amorphous structure with nanometer size and porous structure, which is conducive to the diffusion of lithium ions in battery materials.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a method for preparing an amorphous nano-oxide, which is applied to a negative electrode of a lithium battery, comprising:
[0010] The raw material containing the target metal ion is subjected to coordination reaction with fumaric acid to obtain a metal organic framework material;
[0011] The metal organic framework material is etched with ozone to obtain amorphous nano-oxides corresponding to the target metal ions.
[0012] In an alternative embodiment, the target metal ions include at least one of copper, iron, zinc, manganese, titanium and cobalt.
[0013] In an optional embodiment, the raw material containing the target metal ion is subjected to a coordination reaction with fumaric acid to obtain a metal organic framework material, comprising:
[0014] Dissolving the raw material in water to obtain a first mixed solution;
[0015] dissolving fumaric acid in ethanol to obtain a second mixed solution;
[0016] Mixing the first mixed solution with the second mixed solution to obtain a reaction solution;
[0017] The reaction liquid is subjected to solid-liquid separation treatment, and washed with water and ethanol respectively, and the metal organic framework material is obtained after drying;
[0018] Preferably, the number of washing with water and ethanol is at least 5 times, respectively.
[0019] In an optional embodiment, the step of mixing the first mixed liquid with the second mixed liquid comprises:
[0020] Under room temperature, the first mixed solution and the second mixed solution are mixed and stirred to obtain the reaction solution;
[0021] Preferably, the stirring time is at least 24 hours;
[0022] Preferably, the stirring speed is not less than 750 rpm.
[0023] In an optional embodiment, the step of etching the metal organic framework material with ozone to obtain an amorphous nano-oxide corresponding to the target metal ion includes: placing the metal organic framework material in a ventilation reaction container and etching it with ozone to obtain a crude oxide; wherein the ventilation reaction container is provided with an inlet and an outlet; a mixed gas of O3 and O2 is introduced into the inlet; and the outlet is used for exhausting the gas;
[0024] The amorphous nano-oxide is obtained by washing the crude oxide with ethanol, filtering and drying in sequence.
[0025] In an optional embodiment, the conditions for etching with ozone include:
[0026] The flow rate of the mixed gas of O3 and O2 is 300 mL / min;
[0027] The time for the ozone etching treatment is not less than 2 hours;
[0028] The temperature condition for the ozone etching process is 80°C.
[0029] In an optional embodiment, the concentration of O3 in the mixed gas of O3 and O2 is not less than 15 g / m 3 .
[0030] In a second aspect, the present invention provides an amorphous nano-oxide prepared by the method for preparing the amorphous nano-oxide as described in any one of the aforementioned embodiments.
[0031] In a third aspect, the present invention provides a negative electrode comprising the amorphous nano-oxide as described in the above embodiment.
[0032] In a fourth aspect, the present invention provides an electrical device, comprising the negative electrode as described in the above embodiment.
[0033] The present invention provides a method for preparing an amorphous nano-oxide, which is applied to the negative electrode of a lithium battery, comprising: performing a coordination reaction between a raw material containing a target metal ion and fumaric acid to obtain a metal organic framework material; and etching the metal organic framework material with ozone to obtain an amorphous nano-oxide corresponding to the target metal ion. The preparation method provided by the present invention uses ozone to etch the metal organic framework material to prepare an oxide material, which is used as a negative electrode material for a lithium ion battery. The prepared oxide material is an amorphous structure with a nanometer size and a porous structure, which is conducive to the diffusion of lithium ions in the battery material and effectively improves the cycle performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is the SEM image of MIL-88A(Fe) prepared in Example 1;
[0036] Figure 2 This is a SEM image of the amorphous nano-iron oxide prepared in Example 1;
[0037] Figure 3 This is the XRD pattern of the amorphous nano-iron oxide prepared in Example 1;
[0038] Figure 4 The XRD pattern of the iron oxide prepared in Comparative Example 1;
[0039] Figure 5 The XRD pattern of the iron oxide prepared in Comparative Example 2;
[0040] Figure 6 This is the XRD pattern of the iron oxide prepared in Comparative Example 3. DETAILED DESCRIPTION
[0041] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0042] The present invention provides a method for preparing an amorphous nano-oxide, which is applied to a negative electrode of a lithium battery, comprising:
[0043] Step S1, a raw material containing target metal ions is subjected to coordination reaction with fumaric acid to obtain a metal organic framework material.
[0044] Step S2, etching the metal organic framework material with ozone to obtain amorphous nano-oxides corresponding to the target metal ions.
[0045] The raw material can be a salt of metal ions. The target metal ions are determined based on the requirements of the battery, including factors such as electrochemical performance, cost, environmental impact, and cycle stability.
[0046] In the above step S1, the raw material containing the target metal ion is subjected to a coordination reaction with fumaric acid. Fumaric acid (C4H4O4) is an organic dibasic acid containing two carboxyl groups (-COOH) and can form a stable coordination compound with metal ions. This process involves the formation of a coordination bond between the metal ion and the carboxyl group of the fumaric acid molecule to generate a metal-fumaric acid complex.
[0047] Through this coordination reaction, metal organic framework materials can be obtained. The formation of this ligand helps to control the distribution and aggregation state of metal ions, providing a precursor for the preparation of amorphous nano oxides in the next step. The formation of metal organic framework materials helps to form uniformly distributed metal oxides in the subsequent process, thereby improving the performance of the final product.
[0048] The coordination reaction can be achieved by solution mixing, temperature control and pH adjustment. By precisely controlling the reaction conditions, the formation of the coordination compound can be optimized to obtain the ideal metal organic framework material.
[0049] In the above step S2, the metal organic framework material obtained in step S1 is treated with ozone. Ozone is a strong oxidant that can oxidize organic ligands and may be accompanied by the reduction of metal ions and the formation of amorphous oxides.
[0050] After ozone treatment, amorphous nano-oxides corresponding to the target metal ions can be obtained. Amorphous nano-oxides have potential application value in energy storage and other fields due to their unique structure and properties. Amorphous materials usually have high chemical activity and adjustable electronic structure, which is particularly important for improving electrocatalytic performance.
[0051] Specifically, ozone treatment can be achieved by a special ozone generator and reactor. By controlling the concentration of ozone and the treatment time, the extent of the redox reaction can be precisely controlled to obtain the desired amorphous nano-oxide.
[0052] It should be noted that the metal organic framework material formed by the coordination reaction not only achieves the removal of organic ligands under ozone treatment, but also promotes the reduction of metal ions and the formation of amorphous oxides. This synergistic effect helps to obtain high-performance amorphous nano-oxides. Amorphous nano-oxides have excellent performance in the field of electrocatalysis due to their high chemical activity and adjustable electronic structure, such as high catalytic activity in oxygen evolution reaction.
[0053] It should be noted that the “amorphous” in this embodiment refers to a solid state in which the arrangement of atoms or molecules inside the solid state has no long-range periodicity, that is, lacks the regular repeating pattern commonly seen in crystal structures.
[0054] In summary, the preparation method provided in the embodiments of the present application uses ozone to etch metal-organic framework materials to prepare oxide materials for use as negative electrode materials for lithium-ion batteries. The prepared oxide materials are amorphous structures with nanometer sizes and porous structures, which are beneficial to the diffusion of lithium ions in battery materials and effectively improve the cycle performance of negative electrode materials.
[0055] In some embodiments, the target metal ion includes at least one of copper, iron, zinc, manganese, titanium, and cobalt.
[0056] For example, if the target metal ion is iron, the corresponding raw material may be FeCl3·6H2O.
[0057] In some embodiments, the step S1, wherein a raw material containing target metal ions is subjected to coordination reaction with fumaric acid to obtain a metal organic framework material, comprises:
[0058] Step S11, dissolving the raw material in water to obtain a first mixed solution.
[0059] In the above step, the raw material containing the target metal ions (such as metal salt) is dissolved in water to form a first mixed solution. This is to make the metal ions evenly dispersed in the water to prepare for the subsequent coordination reaction with fumaric acid.
[0060] By dissolving, the metal ions are evenly dispersed in the water to form a uniform first mixed solution. This has the advantage of ensuring that the metal ions are in full contact with the fumaric acid, which is beneficial to the subsequent coordination reaction.
[0061] Step S12, dissolving fumaric acid in ethanol to obtain a second mixed solution.
[0062] In the above steps, ethanol, as a solvent, helps dissolving fumaric acid, and the volatility of ethanol helps the subsequent drying process. The dissolution of fumaric acid in ethanol helps to form a uniform second mixed solution, which is convenient for mixing with the first mixed solution. The volatility of ethanol also helps to remove the solvent in the subsequent steps, reducing the energy consumption in the drying process.
[0063] Step S13, mixing the first mixed liquid and the second mixed liquid to obtain a reaction liquid.
[0064] The above method involves mixing a first mixed solution containing metal ions with a second mixed solution containing fumaric acid to promote the occurrence of a coordination reaction. In the mixed reaction solution, the metal ions and the fumaric acid molecules undergo a coordination reaction to form a metal-fumaric acid complex. The formation of this complex helps to control the distribution and aggregation state of the metal ions, and provides a good precursor for preparing amorphous nano oxides.
[0065] For example, when the target metal ion is an iron ion, the specific coordination reaction is: when the iron ion (Fe 3+ ) is mixed with fumaric acid (C4H4O4), the iron ion can form a coordination bond with the carboxyl group (-COOH) of fumaric acid.
[0066] In this reaction, the iron ion (Fe 3+ ) as the central ion, and the fumaric acid molecule as the ligand, which combines with the iron ion through coordination bonds to form a coordination compound. This coordination compound is usually called a metal organic framework material.
[0067] Step S14, performing solid-liquid separation on the reaction liquid, washing with water and ethanol respectively, and obtaining the metal organic framework material after drying.
[0068] In some embodiments, the number of washings with water and ethanol, respectively, is at least 5 times.
[0069] In the above, the reaction liquid is subjected to solid-liquid separation to separate the metal organic framework material, and is washed with water and ethanol to remove unreacted fumaric acid and by-products. A pure metal organic framework material can be obtained by solid-liquid separation and washing. The washing times can be at least 5 times, which can ensure the thorough removal of by-products and unreacted substances and improve the purity and quality of the product.
[0070] In some embodiments, the method of mixing the first mixed liquid with the second mixed liquid in step S13 includes:
[0071] Step S131, mixing the first mixed solution and the second mixed solution at room temperature, and stirring to obtain the reaction solution;
[0072] In some embodiments, the stirring time is at least 24 hours;
[0073] In some embodiments, the stirring speed is not less than 750 rpm.
[0074] In some embodiments, the step S2, etching the metal organic framework material with ozone to obtain an amorphous nano-oxide corresponding to the target metal ion, comprises:
[0075] Step S21, placing the metal organic framework material in a ventilation reaction container and etching it with ozone to obtain a crude oxide product; wherein the ventilation reaction container is provided with an inlet and an outlet; the inlet is used to introduce a mixed gas of O3 and O2; and the outlet is used to discharge the gas.
[0076] As mentioned above, this step involves placing the metal organic framework material in a closed reaction vessel and etching it by passing a mixed gas of ozone (O3) and oxygen (O2). Ozone, as a strong oxidant, can oxidize organic ligands, which may be accompanied by the reduction of metal ions and the formation of amorphous oxides.
[0077] Through ozone etching treatment, amorphous nano-oxide crude products corresponding to the target metal ions can be obtained. The advantage of using ozone as an oxidant is its high reactivity and selectivity, which can achieve the transformation of organic ligands to amorphous oxides under relatively mild conditions, avoiding structural damage and crystal growth that may be caused by high-temperature heat treatment.
[0078] This can be achieved through a dedicated ozone generator and reactor. By controlling the concentration of ozone and the treatment time, the extent of the redox reaction can be precisely controlled to obtain the desired amorphous nano-oxide.
[0079] Step S22, washing the crude oxide with ethanol, filtering, and drying in sequence to obtain the amorphous nano-oxide.
[0080] As mentioned above, the crude oxide is subsequently treated, including ethanol washing to remove unreacted organic matter and by-products, filtration to separate solid oxide and liquid, and drying to remove residual solvent and moisture. After this series of treatments, pure, dry amorphous nano-oxides can be obtained. Ethanol washing helps to remove organic impurities that may affect the performance of the oxide, filtration ensures the separation of the oxide from the liquid, and drying ensures the stability of the oxide and facilitates subsequent applications.
[0081] The ethanol washing can be accomplished by repeated washing-separation-re-washing processes. Filtration can be accomplished by common filtration techniques such as vacuum filtration. Drying can be accomplished by hot air drying, vacuum drying, and other techniques.
[0082] Taking the target metal ion as iron ion as an example, in step S1, a metal organic framework material, namely MIL-88A (Fe), is obtained. Ozone (O3) is a strong oxidant that can react with the organic part in the metal organic framework material to remove the organic ligand and leave an amorphous metal oxide.
[0083] In this reaction, the coordination compound formed by iron ions and fumaric acid is oxidized under the action of ozone, and the fumaric acid ligand is oxidized and decomposed into carbon dioxide (CO2) and water (H2O), while the iron ions are oxidized to form amorphous iron oxide (FeO x ).
[0084] In some embodiments, the conditions for etching with ozone include:
[0085] The flow rate of the mixed gas of O3 and O2 is 300 mL / min;
[0086] The time for the ozone etching treatment is not less than 2 hours;
[0087] The temperature condition for the ozone etching process is 80°C.
[0088] In some embodiments, the concentration of O3 in the mixed gas of O3 and O2 is not less than 15 g / m 3 .
[0089] In addition, an amorphous nano-oxide is also provided in an embodiment of the present application, which is prepared by the preparation method of the amorphous nano-oxide as described in any of the aforementioned embodiments.
[0090] In addition, an embodiment of the present application further provides a negative electrode, comprising the amorphous nano-oxide as described in the aforementioned embodiment.
[0091] In addition, an electrical device is also provided in an embodiment of the present application, including the negative electrode as described in the above embodiment.
[0092] Example 1
[0093] In this example, a battery was prepared.
[0094] Experimental methods:
[0095] 1. Preparation of metal organic framework materials [MIL-88A (Fe)]:
[0096] (1) Dissolve iron ions: Take 20 mmol (5.406 g) of FeCl3·6H2O and dissolve it in 150 mL of water.
[0097] (2) Dissolving fumaric acid: Dissolve 20 mmol (2.322 g) of fumaric acid in 150 mL of ethanol.
[0098] (3) Mixed solution: The above two solutions were mixed and stirred at 750 rpm for 24 hours at room temperature.
[0099] (4) Solid-liquid separation: Separate the solids by centrifugation.
[0100] (5) Washing: Wash the separated solid with water and ethanol 5 times.
[0101] (6) Drying: Drying the washed solid to obtain the metal organic framework material MIL-88A (Fe).
[0102] Reference Figure 1This is the SEM image of MIL-88A(Fe).
[0103] 2. Etching with ozone:
[0104] (1) Place in reaction vessel: Place 120 mg of MIL-88A(Fe) in a 100 mL two-necked flask.
[0105] (2) Introducing O3 / O2 mixed gas: one port is connected to the O3 / O2 mixed gas (flow rate 300 mL / min), and the other port is used as the gas outlet.
[0106] (3) Setting O3 concentration and treatment conditions: O3 concentration in O3 / O2 mixed gas is 15g / m 3 , the treatment temperature is 80℃ and the treatment time is 2 hours.
[0107] (4) Washing and drying: The treated material is washed with ethanol and filtered, and then dried at 60° C. overnight to obtain an amorphous nano-oxide, i.e., an amorphous nano-iron oxide negative electrode material.
[0108] Reference Figure 2 is the SEM image of amorphous nano-iron oxide; Figure 3 This is the XRD pattern of amorphous nano-iron oxide.
[0109] 3. Preparation of battery electrode materials:
[0110] (1) Mixing materials: 70 wt.% of the prepared amorphous nano-oxide, 15 wt.% of acetylene black and 15 wt.% of PVDF were uniformly mixed to prepare a slurry.
[0111] (2) Coating and molding: The slurry is evenly coated on the copper foil, vacuum dried and then punched into a circular electrode plate.
[0112] 4. Assemble the battery:
[0113] (1) Preparation of electrolyte: Use 1 mol / L LiPF6 in fluoroethylene carbonate, dimethyl carbonate and ethylene carbonate (volume ratio of 10:45:45) as the electrolyte.
[0114] (2) Prepare the diaphragm: Cut the purchased polypropylene film into pieces and use it as the diaphragm.
[0115] (3) Battery assembly: Button cells were assembled in an argon atmosphere in a glove box, using metallic lithium as the counter electrode.
[0116] Example 2
[0117] In this example, a battery was prepared.
[0118] Experimental methods:
[0119] The method is basically the same as Example 1, except that the ozone treatment temperature is 100°C;
[0120] Example 3
[0121] In this example, a battery was prepared.
[0122] Experimental methods:
[0123] It is basically the same as Example 1, except that the ozone treatment time is 1 hour.
[0124] Example 4
[0125] In this example, a battery was prepared.
[0126] Experimental methods:
[0127] The same as Example 1, except that the concentration of O3 in the O3 / O2 mixed gas is 30 g / m 3 .
[0128] Comparative Example 1
[0129] In this comparative example, a battery was prepared.
[0130] Experimental methods:
[0131] 1. Preparation of metal organic framework materials [MIL-88A (Fe)]:
[0132] (1) Dissolve iron ions: Take 20 mmol (5.406 g) of FeCl3·6H2O and dissolve it in 150 mL of water.
[0133] (2) Dissolving fumaric acid: Dissolve 20 mmol (2.322 g) of fumaric acid in 150 mL of ethanol.
[0134] (3) Mixed solution: The above two solutions were mixed and stirred at 750 rpm for 24 hours at room temperature.
[0135] (4) Solid-liquid separation: Separate the solids by centrifugation.
[0136] (5) Washing: Wash the separated solid with water and ethanol 5 times.
[0137] (6) Drying: Drying the washed solid to obtain the metal organic framework material MIL-88A (Fe).
[0138] 2. Calcination to obtain iron oxide:
[0139] Calcination: MIL-88A(Fe) was placed in a muffle furnace and calcined at 600°C in an air atmosphere for 3 hours to obtain iron oxide.
[0140] Reference Figure 4 This is the XRD pattern of the iron oxide prepared in Comparative Example 1.
[0141] 3. Preparation of battery electrode materials:
[0142] (1) Mixing materials: 70 wt.% of the prepared iron oxide material, 15 wt.% of acetylene black and 15 wt.% of PVDF were uniformly mixed to prepare a slurry.
[0143] (2) Coating and molding: The slurry is evenly coated on the copper foil, vacuum dried and then punched into a circular electrode plate.
[0144] 4. Assemble the battery:
[0145] (1) Preparation of electrolyte: Use 1 mol / L LiPF6 in fluoroethylene carbonate, dimethyl carbonate and ethylene carbonate (volume ratio of 10:45:45) as the electrolyte.
[0146] (2) Prepare the diaphragm: Cut the purchased polypropylene film into pieces and use it as the diaphragm.
[0147] (3) Battery assembly: Button cells were assembled in an argon atmosphere in a glove box, using metallic lithium as the counter electrode.
[0148] 5. Battery performance test:
[0149] (1) Constant current charge and discharge test: Perform constant current charge and discharge test on the battery.
[0150] (2) Set voltage range: The charge and discharge voltage range is set to 0.01~3.0V.
[0151] Comparative Example 2
[0152] In this comparative example, a battery was prepared.
[0153] Experimental methods:
[0154] 1. Preparation of iron oxide:
[0155] Calcination of ferric nitrate nonahydrate: Ferric nitrate nonahydrate (Fe(NO3)3·9H2O) was placed in a muffle furnace and calcined at 600°C in an air atmosphere for 3 hours to obtain iron oxide.
[0156] Reference Figure 5 This is the XRD pattern of the iron oxide prepared in Comparative Example 2.
[0157] 2. Preparation of battery electrode materials:
[0158] (1) Mixing materials: 70 wt.% of the prepared iron oxide material, 15 wt.% of acetylene black and 15 wt.% of PVDF were uniformly mixed to prepare a slurry.
[0159] (2) Coating and molding: The slurry is evenly coated on the copper foil, vacuum dried and then punched into a circular electrode plate.
[0160] 3. Assemble the battery:
[0161] (1) Preparation of electrolyte: Use 1 mol / L LiPF6 in fluoroethylene carbonate, dimethyl carbonate and ethylene carbonate (volume ratio of 10:45:45) as the electrolyte.
[0162] (2) Prepare the diaphragm: Cut the purchased polypropylene film into pieces and use it as the diaphragm.
[0163] (3) Battery assembly: Button cells were assembled in an argon atmosphere in a glove box, using metallic lithium as the counter electrode.
[0164] Comparative Example 3
[0165] In this comparative example, a battery was prepared.
[0166] Experimental methods:
[0167] It is basically the same as Example 1, except that the temperature of ozone O3 treatment is 60°C.
[0168] Reference Figure 6 This is the XRD diagram of the iron oxide prepared in Comparative Example 3.
[0169] Test experiment:
[0170] 1. Test method:
[0171] The specific surface area of the materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was tested;
[0172] The batteries prepared in Example 1 and Comparative Examples 1 to 3 were subjected to the following battery performance tests:
[0173] (1) Constant current charge and discharge test: Perform constant current charge and discharge test on the battery.
[0174] (2) 50-cycle capacity retention test, the charge and discharge voltage range is set to 0.01V~3.0V.
[0175] 2. Test results and analysis:
[0176] Experimental results:
[0177] Table 1 shows the test results of specific surface area of the negative electrode materials prepared in the examples and comparative examples and the test results of battery performance.
[0178] Table 1. Performance test results of embodiments and comparative examples
[0179] sample <![CDATA[Specific surface area m 2 / g]]> First discharge specific capacity (mAh / g) 50 cycles capacity retention rate (%) Example 1 212.2 1206.9 78.2 Example 2 120.5 \ \ Example 3 197.6 \ \ Example 4 202.5 \ \ Comparative Example 1 23.4 791.3 55.3 Comparative Example 2 16.1 929.6 42.3 Comparative Example 3 37.8 549.6 41.6
[0180] analyze:
[0181] (1) Referring to the data in Table 1, the amorphous nano-oxide negative electrode materials prepared in Examples 1 to 4 have high specific surface areas, which are 212.2 m 2 / g, 120.5m 2 / g, 197.6m 2 / g, 202.5m 2 / g. A high specific surface area means that the material has more apparent reaction area, which can increase the contact area between the electrode material and the electrolyte, which is beneficial to the diffusion and reaction rate of ions, thereby potentially increasing the capacity and power of the battery.
[0182] The specific surface areas of the iron oxide negative electrode materials prepared in Comparative Examples 1 to 3 are all relatively low, being 23.4 m 2 / g, 16.1m 2 / g, 37.8m 2 This indicates that the apparent reaction area of the material in the control example is small, which is not conducive to ion diffusion and reaction rate, and greatly affects the battery performance.
[0183] (2) The first discharge specific capacity of the battery was investigated for Example 1 and Comparative Examples 1 to 3. The first discharge specific capacity of the battery prepared in Example 1 was 1206.9 mAh / g, which is the highest value among all the examples and comparative examples, indicating that the amorphous nano-oxide in Example 1 has excellent lithium storage capacity.
[0184] The first discharge specific capacities of Comparative Examples 1 and 2 are 791.3 mAh / g and 929.6 mAh / g, respectively, which are lower than those of Example 1, indicating that the lithium storage capacity of the iron oxide material in the comparative example is not as good as that of Example 1.
[0185] (3) In the investigation of the 50-cycle capacity retention rate, the 50-cycle capacity retention rate of Example 1 is 78.2%, which is the highest value among all the examples and comparative examples, indicating that the amorphous nano-oxide in Example 1 has good cycle stability.
[0186] The 50-cycle capacity retention rates of Comparative Examples 1 to 3 are 55.3%, 42.3%, and 41.6%, respectively, all lower than Example 1, indicating that the cyclic stability of the iron oxide material in the comparative example is poor.
[0187] MIL-88A(Fe) itself is a nanomaterial with a microporous structure. After ozone oxidation etching, the iron oxide not only maintains the original MOF morphology and nanosize, but also can produce more micropores and mesopores, and the surface is concave to a certain extent. This rough porous structure is conducive to the transmission of lithium ions, further increasing the activation area of the material and the contact area with the electrolyte, thereby improving its capacity and cycle retention rate.
[0188] In addition, ozone cannot completely oxidize the organic ligands in MOF, and the residual trace carbon can further improve the conductive properties of the material.
[0189] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an amorphous nano-oxide, applied to a negative electrode of a lithium battery, characterized in that: include: The raw material containing the target metal ion is subjected to coordination reaction with fumaric acid to obtain a metal organic framework material; The metal organic framework material is etched with ozone to obtain amorphous nano-oxides corresponding to the target metal ions.
2. The method for preparing the amorphous nano-oxide according to claim 1, characterized in that: The target metal ions include at least one of copper, iron, zinc, manganese, titanium and cobalt.
3. The method for preparing the amorphous nano-oxide according to claim 1, characterized in that: The method of carrying out coordination reaction between the raw material containing the target metal ion and fumaric acid to obtain the metal organic framework material comprises: Dissolving the raw material in water to obtain a first mixed solution; dissolving fumaric acid in ethanol to obtain a second mixed solution; Mixing the first mixed solution with the second mixed solution to obtain a reaction solution; The reaction liquid is subjected to solid-liquid separation treatment, and washed with water and ethanol respectively, and the metal organic framework material is obtained after drying; Preferably, the number of washing with water and ethanol is at least 5 times, respectively.
4. The method for preparing the amorphous nano-oxide according to claim 3, characterized in that: The method of mixing the first mixed liquid with the second mixed liquid comprises: Under room temperature, the first mixed solution and the second mixed solution are mixed and stirred to obtain the reaction solution; Preferably, the stirring time is at least 24 hours; Preferably, the stirring speed is not less than 750 rpm.
5. The method for preparing the amorphous nano-oxide according to claim 1, characterized in that: The step of etching the metal organic framework material with ozone to obtain an amorphous nano-oxide corresponding to the target metal ion includes: The metal organic framework material is placed in a ventilation reaction container and etched with ozone to obtain a crude oxide product; wherein the ventilation reaction container is provided with an inlet and an outlet; the inlet is used to introduce a mixed gas of O3 and O2; and the outlet is used to discharge the gas; The amorphous nano-oxide is obtained by washing the crude oxide with ethanol, filtering and drying in sequence.
6. The method for preparing the amorphous nano-oxide according to claim 5, characterized in that: The conditions for etching with ozone include: The flow rate of the mixed gas of O3 and O2 is 300 mL / min; The time for the ozone etching treatment is not less than 2 hours; The temperature condition for the ozone etching process is 80°C.
7. The method for preparing amorphous nano-oxide according to claim 5, characterized in that: The concentration of O3 in the mixed gas of O3 and O2 is not less than 15g / m 3 .
8. An amorphous nano-oxide, characterized in that: The amorphous nano-oxide is prepared by the preparation method of any one of claims 1 to 7.
9. A negative electrode, characterized in that Comprising the amorphous nano-oxide as claimed in claim 8.
10. An electrical equipment, characterized in that: Comprising the negative electrode as claimed in claim 9.
Citation Information
Cited By
Nano transition metal oxide, gas-phase synthesis method and application
CN119706750A
Nano-transition metal oxides, gas-phase synthesis method and application
CN119706750B